Comparison of the structural characterizatics and physicochemical properties of starches from sixteen cassava germplasms cultivated in China. Issue 1 (1st January 2020) - He, Rui; Fu, Nai-Fang; Chen, Hai-Ming; Ye, Jian-Qiu; Chen, Li-Zhen; Pu, Yun-Feng; Zhang, Wei-Min
ABSTRACT: Starches from sixteen cassava germplasms harvested at the same time in the Hainan region were evaluated for their physicochemical and structural properties. The granule morphology of all the isolated cassava starch samples showed round, bell or oval shapes and exhibited the same A-type crystalline pattern. The crystallinity range was 26.6–30.8%. The selected cassava germplasms showed a wide variation in granule size distribution: The D[4, 3] (the average particle size) ranged from 13.49 μm to 306.27 μm. The water absorption capacity (192.6–226.7%), oil absorption capacity (185.0–216.9%) and transparency (6.8–16.5%) indices varied significantly among the cassava germplasms. However, the retrogradation rates of the cassava starch pastes increased rapidly during the first 1 h and then stabilized. The solubility of starch increased with the temperature. In addition, the FTIR (Fourier Transform Infrared Spectrometer) ratios of 1045/1022 cm −1 and 1022/995 cm −1 of the sixteen cassava starches varied in the range of 1.06–1.78 and 0.78–1.04, respectively. These results indicated that the granule size, relative crystallinity, degree of short-range order, water and oil absorption capacities, solubility and transparency of the cassava starches were greatly influenced by the variety of cassava, which could help in determining the advantages of these starches for applications in different food and nonfood industries.